Parents' awareness and perception of the polio eradication programme in Gombe Local Government Area, Gombe State, Nigeria (2007)
The polio eradication programme currently present in Nigeria has not resulted in the complete eradication of the disease. This has prompted an investigation into the awareness and perception of recipients of the programme in Gombe Local Government Area (LGA), Gombe State. The survey sample size was 422 parents. These were selected via a multistage sampling system. An additional 24 parents and 6 community leaders were purposely selected to participate in focus group discussions and interviews. The results showed that while the majority of parents (353, 83.6%) believed that polio was a serious disease, only 216 (50.7%) parents believed their children were susceptible. Fifty-six per cent of respondents did not know the mode of transmission of the polio virus. The major reasons cited for reluctance to release children for polio immunisation were: 165 (39.6%) parents were worried about polio vaccine overdose, 31 (7.3%) believed the vaccine was mixed with harmful pathogens, and 172 (40.8%) felt there were too many national immunisation days and too much attention was given to polio to the detriment of other diseases. Based on these findings, there is the need for a campaign to educate parents on the nature of the polio disease, to highlight the importance of immunisation and to dispel negative rumours regarding the immunisation programme.